Partisipasi Politik dalam Pembangunan Desa di Kecamatan Sayan Kabupaten Melawi - Padilah, Ahirul Habib; Fayuni, Dayang Febby; Nurviyanti, Milanda Dwi (Journal of Social and Policy Issues, 2023)
The Politics of Empowering the Community in village development in the Sayan District is crucial in enhancing active citizen participation in the policy-making process, decision-making, and implementation of village development programs. Political participation in the Sayan District can take the form of direct participation through village meetings, participation through representative mechanisms, as well as participation through collective action and advocacy. Strong political participation can reinforce the independence of the village in managing natural, social, and economic resources in the Sayan District. Through political participation, residents can voice their interests and aspirations, making policies and village development programs more responsive to the needs and expectations of the residents. Additionally, political participation can also improve accountability and transparency in village financial management and the development of village infrastructure in the Sayan District. However, there are challenges in promoting political participation in villages in the Sayan District, such as the lack of awareness among the community about the importance of political participation, limited access to information, and the insufficient skills and capacities of the community in managing village resources. Therefore, efforts are needed to strengthen community political participation in the Sayan District, including enhancing political literacy, developing inclusive participation mechanisms, and empowering village communities in sustainable resource management